2D material programming for 3D shaping - Amirali Nojoomi (Nature Portfolio, 2021)
Two-dimensional (2D) growth-induced 3D shaping enables shape-morphing materials for diverse applications but quantitative design of 2D growth for arbitrary 3D shapes remains challenging. Here, the authors show a 2D material programming approach for arbitrary 3D shaping, which prints hydrogel sheets encoded with spatially controlled in-plane growth and transforms them to programmed 3D structures.